T3 The Effect Of Electronic Cigarette Exposure On Innate Immune Cells. (10th November 2014) - Higham, AJ; Rattray, NJW; Dewhurst, JA; Singh, D
Abstract : Introduction: Are electronic cigarettes (e-cigs) safe? The long-term effects of e-cigs are unknown. E-cigs contain a variety of substances that may be harmful to the lungs. We hypothesised that e-cigs have the potential to cause pulmonary inflammation. We have investigated the effects of e-cigs on human innate immune cells in vitro . Methods: Blood neutrophils from six healthy non-smokers were exposed to e-cig vapour extract (ECVE) for 6 hr. MMP-9 and CXCL8 release were measured by ELISA and MMP-9 activity was measured by zymography. p38 MAPK activation was also measured, along with neutrophil shape change and CD11b and CD66b expression by flow cytometry. Finally, we measured CXCL8 release from alveolar macrophages isolated from resected lung tissue from three ex-tobacco smokers exposed to ECVE for 24 hr. Results: Exposure of neutrophils to ECVE increased MMP-9 and CXCL8 release with the maximal effect observed at an optical density (OD) of 0.003 (Table 1 ). This was observed along with an increase in MMP-9 gelatinase activity and increased p38 MAPK activation. Furthermore, neutrophil shape change, and dual CD11b and CD66b expression increased in response to ECVE treatment compared to untreated cells. Following a similar trend, 0.003 (OD) ECVE caused an increase in CXCL8 release from alveolar macrophages. Discussion: We have shown that e-cig exposure causes an inflammatory response from neutrophils and macrophages. The effects discussed here are similar to those caused by tobacco cigarettes. Based on these findings, the use of e-cigs may pose a risk to public health.